High temperature annealing and CVD growth of few‐layer graphene on bulk AlN and AlN templates. Issue 4 (17th January 2017) - Dagher, R.; Matta, S.; Parret, R.; Paillet, M.; Jouault, B.; Nguyen, L.; Portail, M.; Zielinski, M.; Chassagne, T.; Tanaka, S.; Brault, J.; Cordier, Y.; et al.
Abstract : Graphene and AlN are promising materials, interesting to combine together. In this study, we will present first results for direct growth of graphene on bulk AlN and on AlN templates using chemical vapor deposition, including the annealing of these substrates at high temperatures. Atomic force microscopy (AFM) enabled us to study the evolution of the AlN surface morphology after annealing and growth. Few‐layer graphene deposition is demonstrated on the basis of X‐ray photoemission and Raman spectroscopy. AFM view of graphene wrinkles on the N‐face of bulk AlN.